The Role of PTX3 in Mineralization Processes and Aging-Related Bone Diseases - Tarantino, Umberto; Greggi, Chiara; Cariati, Ida; Visconti, Virginia Veronica; Gasparini, Monica; Cateni, Marco; Gasbarra, Elena; Botta, Annalisa; Salustri, Antonietta; Scimeca, Manuel (Frontiers in Immunology, 2021)
The Long Pentraxin 3 (PTX3) is a multifunctional glycoprotein released by peripheral blood leukocytes and myeloid dendritic cells in response to primary pro-inflammatory stimuli, that acts as a non-redundant component of the humoral arm of innate immunity. In addition to the primary role in the acute inflammatory response, PTX3 seems to be involved in other physiological and pathological processes. Indeed, PTX3 seems to play a pivotal role in the deposition and remodeling of bone matrix during the mineralization process, promoting osteoblasts differentiation and activity. Recently, PTX3 was seen to be involved in the ectopic calcifications’ formation in breast cancer disease. In this regard, it has been observed that breast cancer tumors characterized by high expression of PTX3 and high amount of Breast Osteoblast Like Cells (BOLCs) showed several Hydroxyapatite (HA) microcalcifications, suggesting a likely role for PTX3 in differentiation and osteoblastic activity in both bone and extra-bone sites. Furthermore, given its involvement in bone metabolism, several studies agree with the definition of PTX3 as a molecule significantly involved in the pathogenesis of age-related bone diseases, such as osteoporosis, both in mice and humans. Recent results suggest that genetic and epigenetic mechanisms acting on PTX3 gene are also involved in the progression of these diseases. Based on these evidences, the aim of our systemic review was to offer an overview of the variety of biological processes in which PTX3 is involved, focusing on bone mineralization, both in a physiological and pathological context.